Android Educational Game for Pancasila and Civic Education Learning - Haris Abdullah Fasha; Santi Ika Murpratiwi; Moh. Ali Albar; Ni Luh Putu Agetania (Journal of Computer Science and Informatics Engineering (J-Cosine), 2024)
In the digital era, traditional teaching methods often fail to engage students, especially in Pancasila and Civic Education. Lack of understanding of Pancasila values leads to declines in religious, humanitarian, and unity values among students, evidenced by frequent fights and bullying. To address this, an interactive Android-based game, "Cerdas Pancasila," was developed with quizzes and puzzles to enhance students' understanding of Pancasila values. Using the Digital Game-Based Learning (DGBL) method, the study included five phases: analysis, design, development, quality assurance, and implementation. The analysis phase identified the need for engaging educational media for students aged 9 to 12. The design phase outlined instructional goals, and the development phase used Android Studio with Kotlin and Java to create the game prototype, which was distributed as a .apk file in the implementation phase. Quality assurance involved alpha and beta testing, resulting in a 90.2% acceptance rate, with 17 out of 18 students stating the game increased their knowledge about Pancasila.